The Use of Writing Assistance Tools in Writing Assignments: Students’ Perspectives - Silitonga, Julianthi Zefana; Fikri, Muhammad Subhan; Sujiyani, Erma; Lestari, Tiarannisa Putri (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2025)
Students often face difficulties in academic writing, especially in achieving grammatical accuracy, clear structure, and coherence. These challenges are more evident for Indonesian EFL learners, who have limited exposure to English and often struggle with grammar, vocabulary, and idea organization. With the advancement of technology, writing assistance tools such as Grammarly, DeepL, and QuillBot have emerged to help students improve their writing quality. The interviews were conducted in the Indonesian language and lasted approximately 15-20 minutes each for the participants. The collected data were analyzed using thematic analysis (Braun & Clarke, 2006) to identify recurring patterns and central themes related to students’ perceptions. Although the data were obtained through participants’ personal narratives, thematic analysis was chosen because the study focuses on perceptions rather than reconstructing life stories. The findings indicate that Grammarly is the most commonly used tool, followed by QuillBot and DeepL. Participants reported that these tools are beneficial for improving writing accuracy, saving time, boosting confidence, and reducing stress. However, the study is limited by its relatively small sample size and the reliance on self-reported experiences, which may restrict the generalizability of the findings.